White-tailed deer population declines in a high-prevalence chronic wasting disease region of Arkansas, USA - Heather E. Gaya; Marcelo H. Jorge; Lisa A. Jorge; Mark G. Ruder; Gino J. D’Angelo; Richard B. Chandler; Michael J. Chamberlain (PLoS ONE, 2026)
Chronic wasting disease (CWD) is a fatal transmissible spongiform encephalopathy affecting cervids worldwide. CWD was first detected in Arkansas in 2015 and as of August 2025 has been detected in 24 counties across the state. Within the Tier 1 CWD management zone of northern Arkansas, average apparent CWD prevalence exceeded 25% at the onset of our study in 2021. We tested the hypothesis that high prevalence of CWD negatively affects white-tailed deer population viability. We collected data from 243 camera traps and deployed GPS-collars on 131 adult deer to monitor population dynamics. Using spatial mark-resight models, we estimated density of adult deer from 2021 to 2024 at three sites across a presumed CWD gradient to assess the impacts of high CWD prevalence on deer abundance. Deer densities declined at all three study sites, at an average 17% (95% CI: 8% − 24%) decline per year. Male densities declined by an average 23% (95% CI: 5% − 31%) per year compared to 15% (95% CI: 2% − 23%) yearly declines for females. These findings suggest that CWD can negatively impact deer populations through direct reductions in density, but additional research is needed to determine if additional factors contributed to these declines. Furthermore, our findings suggest the populations we studied are not sustainable under current harvest regulations.